Analisis Kualitas Pelayanan Menggunakan Metode Importance Performance Analysis (IPA) Studi Kasus pada Cafe XYZ - Desi Desi; Fina Aprilia; Simaludin Andiyansyah; Anne Kurniawati; Endang Silaningsih (STIKes Ibnu Sina Ajibarang, 2025)
The research has the aim of evaluating customer satisfaction with the aim of identifying service areas that must be improved and maintained. The Importance Performance Analysis (IPA) method is applied to compare the level of importance (expectations) with the performance of services provided by Cafe XYZ to customers. The results of this study were analysed and visualised in a Cartesian diagram, where there are 9 customer service attributes that are considered important, spread across two quadrants: 5 attributes are in quadrant A and 4 attributes are in quadrant. Evaluation of customer satisfaction with Cafe XYZ services is measured by the Customer Satisfaction Index (CSI) method. The results showed that most consumers were satisfied with the services provided. Nevertheless, the company needs to continue to improve its service performance to achieve an optimal level of customer satisfaction.